Temporospatial dissociation of Pe subcomponents for perceived and unperceived errors - Endrass, Tanja; Klawohn, Julia; Preuss, Julia; Kathmann, Norbert (Frontiers in Human Neuroscience, 2012)
Previous research on performance monitoring revealed that errors are followed by an initial fronto-central negative deflection (error-related negativity, ERN) and subsequently centro-parietal positivity (error positivity, Pe). It has been shown that error awareness mainly influences the Pe, whereas the ERN seems unaffected by conscious awareness of an error. The aim of the present study was to investigate the relation of ERN and Pe to error awareness in a visual size discrimination task in which errors are not elicited by impulsive responding but by perceptual difficulty. Further, we applied a temporospatial principal component analysis (PCA) to examine whether the temporospatial subcomponents of the Pe would differentially relate to error awareness. ERP results were in accordance with earlier studies: a significant error awareness effect was found for the Pe, but not for the ERN. Interestingly, a modulation with error perception on correct trials was found: correct responses considered as incorrect had larger correct-related negativity (CRN) and lager Pe amplitudes than correct responses considered as correct. The PCA yielded two relevant spatial factors accounting for the Pe (latency 300 ms). A temporospatial factor displaying a centro-parietal positivity varied significantly with error awareness. Of the two temporospatial factors corresponding to response-related negativities, a factor with central topography varied with response correctness and subjective error perception on correct responses. The PCA results indicate that the error awareness effect is specifically related to the centro-parietal subcomponent of the Pe. Since this component has also been shown to be related to the importance of an error, the present variation with error awareness indicates that this component is sensitive to the salience of an error and that salience secondarily triggers error awareness.